Bio-Based Concrete Enhancement for Sustainable Construction - Venkata Siddhartha Raju Vegesna; Dr. D. Balaji (International Journal of Scientific Research in Civil Engineering, 2025)
The construction industry significantly contributes to carbon emissions and resource depletion, necessitating innovative approaches for sustainable concrete production. This study explores bio-based enhancements, focusing on Microbial Induced Calcite Precipitation (MICP) and Algae-Based CO₂ Sequestration to improve concrete’s structural performance and environmental sustainability. MICP utilizes bacteria (Sporosarcina pasteurii) to induce calcite precipitation, enhancing self-healing properties and strength. Algae-based admixtures and biochar offer a natural solution for CO₂ absorption during curing, reducing the carbon footprint. The proposed bio-based concrete solutions are evaluated based on strength, durability, permeability, and sustainability metrics. Experimental validation demonstrates that these enhancements improve mechanical properties, reduce environmental impact, and promote long-term durability compared to conventional concrete. This study contributes to green construction practices by integrating biological systems with modern materials for eco-friendly and resilient infrastructure.